Status Dan Keanekaragaman Fungi Mikoriza Arbuskula di Lahan Agroforestri - Rahmat Saputra; Nurheni Wijayanto; Irdika Mansur (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2020)
Coffee is one of the leading commodities in Indonesia. These plants are usually cultivated with agroforestry systems. The agroforestry system was chosen because it can increase crop productivity. But there are still many factors that can affect productivity such as Arbuscular Mycorrhizal Fungi (AMF). This study aims to analyze the relationship between the number of spores, the percentage of colonization, and the diversity of AMF. The result showed that the highest percentage of colonization and the number of spores found in land 3. The agroforestry component affects the presence of AMF. The percentage of colonization and the number of spores from AMF is generally directly proportional. Diversity of AMF spores morphological type, among others Glomus has 9 forms, Acaulospora has 5 forms, Dentiscutata has 5 forms, Entrophospora has 4 forms, and Gigaspora has 1 form. Keywords: Acaulospora, Dentiscutata, Entrophospora, Gigaspora, Glomus